Changing in National Infrastructure Policy: How It Affect Indonesia’s Economy? Case Study of Indonesia 2010 and 2016 IO Table and 2016 IRIO Table - Ade Marsinta Arsani; Chaoqing Huang (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
This research would like to firstly figure out how new infrastructure policy affects national economic structure changes, and secondly figure out does the new policy effect on inter-regional economy linkage. This study uses economic structure, growth decomposition, location quotient, and linkage analysis on Input-output table to indicate national and inter-regional level economic changes between 2010 and 2016 in Indonesia. We find that economic structure generally remains the same, only transportation and real estate sector increased their contribution, this may indicate the beginning of infrastructure development stage. During 2010 to 2016, the growth was led by the expansion of domestic demand in almost all sectors, however in some sectors the technological changes have a negative contribution. Furthermore, the two most linked sectors are manufacturing and electricity sectors. Inter-regional analysis indicated that Java and Sumatera have more power and sensitivity level compared to other regions. The suggestion to booster economy development is to implement technological process and publish policy considering regional characteristics may accelerate economic equity across regions.